2016
DOI: 10.1186/s13054-016-1528-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of extracerebral organ failure on outcome of patients after cardiac arrest: an observational study from the ICON database

Abstract: BackgroundWe used data from a large international database to assess the incidence and impact of extracerebral organ dysfunction on prognosis of patients admitted after cardiac arrest (CA).MethodsThis was a sub-analysis of the Intensive Care Over Nations (ICON) database, which contains data from all adult patients admitted to one of 730 participating intensive care units (ICUs) in 84 countries from 8–18 May 2012, except admissions for routine postoperative surveillance. For this analysis, patients admitted aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 35 publications
3
28
0
1
Order By: Relevance
“…The SOFA scores displayed an acceptable discriminatory power for survivors, at admission, with an AUC value of 0.634, which was consistent with that of previously conducted studies [ 8 , 15 , 16 ]. Respiratory, cardiovascular and neurological dysfunction were the most commonly observed types of organ dysfunction, as observed in our study patients; this is also similar to the results of previously conducted studies.…”
Section: Discussionsupporting
confidence: 89%
“…The SOFA scores displayed an acceptable discriminatory power for survivors, at admission, with an AUC value of 0.634, which was consistent with that of previously conducted studies [ 8 , 15 , 16 ]. Respiratory, cardiovascular and neurological dysfunction were the most commonly observed types of organ dysfunction, as observed in our study patients; this is also similar to the results of previously conducted studies.…”
Section: Discussionsupporting
confidence: 89%
“…Few studies have reported data on the development of liver dysfunction after CA; in one large database, liver failure, defined using only bilirubin levels, occurred in 10% of CA patients on ICU admission and in up to 20% during the ICU stay, with no differences between patients with favourable or unfavourable neurological outcome [ 18 ]. The occurrence of ALF in our study is quite high; however, some high bilirubin levels may have been due to hemolysis or rhabdomyolysis and increased INR levels could have been secondary to sepsis or previous anticoagulant therapy, which may have resulted in an overestimation of the number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that HH was also a significant predictor of poor neurologic outcome after CA, and previous studies have described an association of HH with mortality in the same setting [ 8 , 19 ]. In two studies [ 5 , 18 ], hepatic failure, assessed by the hepatic SOFA score, was not associated with mortality; however, this score does not consider AST/ALT as a relevant marker of hepatic damage induced by anoxia. Our findings showing a role of HH and AKI as predictors of unfavourable neurological outcome support the need to better describe the occurrence of extra-cerebral organ dysfunction among patients admitted to the ICU after CA.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that unfavorable versus favorable neurological outcomes were associated with multiorgan failure syndrome on admission and during in-hospital stay, but independent predictors of unfavorable neurological outcome were MV on admission, high admission Simplified Acute Physiology Score (SAPS) II score, and neurological dysfunction on admission [24]. In our OHCA patients with ischemic brain injury, we observed significantly more likely the use of noradrenalin, dobutamine and MV, reflecting respiratory and cardiovascular failure in these patients.…”
Section: Discussionmentioning
confidence: 59%